Sams Teach Yourself HTML 4 in 24 Hours, Fourth Edition - Oliver, Dick (Sams, 1999)
Sams Teach Yourself HTML 4 in 24 Hours, Fourth Edition, is a carefully organized tutorial that teaches the beginning Web page author just what you need to know in order to get a Web page up in the shortest time possible. The book covers only those HTML tags and technologies that are likely to be used on a beginner's Web page, and it is organized in a logical step-by-step order. This new edition updates coverage of new Web publishing technologies. Refined and reworked parts of the book to make it even more clear and straightforward for beginners.